Face Recognition for Motorcycle Engine Ignition with Messaging System - Austria, Yolanda D.; Lacatan, Luisito L.; Funtera, John Gregory D.; Montenegro, Jonet H.; Santelices, Laymar T. (International Journal of Computing Sciences Research; Vol 1 No 3 (2017): Vol 1, No 3, 2017)
Purpose – In this current world where technology is growing up day by day and scientific researchers are presenting new era of discoveries, the need for security is also increasing in all areas. At present, the vehicle usage is basic necessity for everyone. Simultaneously, protecting the vehicle against theft is also very important. Traditional vehicle security system depends on many sensors and cost is also high. When the vehicle is stolen, no more response or alternative could be available to help the owner of the vehicle to find it back. The main goal of this paper is to protect the vehicle from any unauthorized access, using fast, easy-to-use, clear, reliable and economical face recognition technique. Method – An efficient automotive security system is implemented for anti-theft using an embedded system for starting the engine by the use of face recognition and integrated with Global Positioning System (GPS) and Global System for Mobile Communication (GSM). This proposed work is an attempt to design and develop a smart anti-theft system that uses Face recognition, GPS and GSM system to prevent theft and to determine the exact location of vehicle. Results – The acceptance test of Face Recognition System for authentication of engine ignition acceptance test#1 shows that the system can recognize the faces of the registered user and ignite the engine. The USB webcam will capture the image of an unregistered/unauthorized user who tried to start the engine and send a text warning notification with an image to the user. The acceptance test of GPS and GSM for location and anti-theft notification acceptance test#1 shows that the GPS can receive the latitude and longitude values of its current location. The GSM can send the current location which had been received by the GPS as text message to user and also send an anti-theft notification if the motorcycle had been moved from its initial to approximately 5 m while engine is off. Conclusion – This study concludes that in order to achieve the prevention of crashing of the system, the Face Recognition System for authentication of engine ignition acceptance test#1 should have an indicator to know if the program is executed successfully. Also, in order to achieve receiving the exact location of the motorcycle, the GPS and GSM for location and anti-theft notification acceptance test#1 should have an antenna in order for the GPS to receive the coordinates from the satellites much more accurate than that of without antenna. Lastly, in order to achieve the error prevention in receiving text messages of the GSM module, the Engine Ignition by Passcode and GSM acceptance test#1 should always delete received messages to clear the allotted memory storage for messages. Recommendations – This study recommends further improvements in terms of security measures and integration of smart systems.